Relevansi Slippery Slope Theory Ditinjau Dari Perspektif Gender Wajib Pajak - I Nyoman Putra Yasa; Sunitha Devi; I Putu Hendra Martadinata (InFestasi, 2020)
This study aims to reveal the potential causes of the phenomenon of increasing taxpayer compliance in Bali which was previously very difficult to achieve. This study examines the relevance of the slippery slope theory in terms of taxpayer's gender perspective through testing the impact of different conditions of taxpayer trusts and tax authorities on mandatory compliance tax, and the impact of gender differences on taxpayer behavior in certain conditions of trust and power, which also affects the level of tax compliance. This research was carried out by using the experimental method with a 2x2x1 design. The experimental participants consisted of taxpayers who were purposive sampling selected, which were then grouped into four main groups based on treatment variables and gender. Further data analysis will be carried out quantitatively using the two-way analysis of variance (ANOVA) method. The results of this study indicate that taxpayers’ trust in the tax authority is the most important factor in encouraging taxpayers’ compliance to pay taxes voluntarily, and is able to suppress individual opportunist behavior caused by gender differences of the taxpayers